Current trends in the immunotherapy of metastatic and recurrent squamous cell carcinoma of the head and neck - Kostalanova, Yu. V.; Ganina, K. A.; Makhonin, A. A.; Gabrielyan, A. G. (Opukholi golovy i shei, 2020)
The immune system plays a key role in the development and progression of head and neck squamous cell carcinoma. Understanding the dysregulation and blockage of the immune system of malignant tumors in this location can improve treatment outcomes. A special group is made up of patients who have a widespread process and relapse after chemotherapy with platinum drugs, because they have a very poor prognosis and limitations in the possibilities of further treatment. To date, the most important data relate to drugs acting on the PD-1 (programmed cell death protein 1)/PD-L1 (programmed death ligand 1) immune checkpoints, which are used by the tumor to block the immune system, which have allowed to increase the effectiveness of treatment. The article presents a clinical case demonstrating the effectiveness of the use of checkpoint inhibitors after the use of platinum preparations.